The Analysis of Inequality in the Bretton Woods Institutions - Ferreira, Francisco H. G. (World Bank, Washington, DC, 2022)
This paper assesses the evolution of thinking, analysis, and discourse about inequality in the World Bank and the International Monetary Fund since their inception in 1944, on the basis of bibliometric analysis, a reading of the literature, and personal experience. Whereas the Fund was largely unconcerned with economic inequality until the 2000s but has shown a rapidly growing interest since then, the Bank’s approach has been characterized by ebbs and flows, with five phases being apparent. The degree of interest in inequality in the two institutions appears to be largely determined by the prevailing intellectual profile of the topic in academic research, particularly in economics, and by ideological shifts in major shareholder countries, propagated downward internally by senior management. Data availability, albeit partly endogenous, also plays a role. Looking ahead, World Bank and International Monetary Fund researchers continue to have an important role to play, despite a much more crowded field in inequality research. The paper suggests that this role involves holding firm to an emphasis on inequality “at the bottom” and highlighting four themes that may deserve special attention.